Recruiting, interviewing, selecting & orienting new employees - Arthur, Diane (AMACOM, American Management Association, 2006)
"Recruiting, Interviewing, Selecting & Orienting New Employees is a practical and user-friendly guide to the entire employment process. Written and designed for daily use in both high-volume and smaller hiring environments, the book includes step-by-step guidelines; specific interview and reference questions to ask (plus the ones to avoid); and information on powerful new electronic recruiting strategies, more effective orientation programs, and more." "The book covers the entire employment process and includes hundreds of sample questions to use as is or adapt to your specific needs. You'll also find a selection of targeted forms and checklists that will help keep your hiring initiatives humming along."--Jacket